Oxygenation Performance of Different Non-Invasive Devices for Treatment of Decompression Illness and Carbon Monoxide Poisoning - Köhler, Andrea; Zoll, Felicitas M.; Ploner, Thomas; Hammer, Alexander; Joannidis, Michael; Tilg, Herbert; Finkenstedt, Armin; Hartig, Frank (Frontiers in Physiology, 2022)
Study Objective: Application of high concentrations of oxygen to increase oxygen partial pressure (pO2) is the most important treatment for patients with carbon monoxide intoxication or divers with suspected decompression illness. The aim of this study was to evaluate the oxygenation performance of various non-invasive oxygen systems. Methods: The effect of different oxygen systems on arterial pO2, pCO2 and pH and their subjective comfort was evaluated in 30 healthy participants. Eight devices were included: nasal cannula, non-rebreather mask, AirLife Open mask, Flow-Safe II CPAP device, SuperNO2VA nasal PAP device, all operated with 15l/min constant flow oxygen; nasal high-flow (50 l/min flow, 1.0 FiO2), non-invasive positive pressure ventilation (NPPV, 12 PEEP, 4 ASB, 1.0 FiO2) and a standard diving regulator (operated with pure oxygen). Results: Diving regulator, SuperNO2VA, nasal high-flow and NPPV achieved mean arterial pO2 concentrations between 538 and 556 mm Hg within five minutes. The AirLife Open mask, the nasal cannula and the non-rebreather mask achieved concentrations of 348 - 451 mm Hg and the Flow-Safe II device 270 mm Hg. Except for the AirLife open mask, pCO2 decreased and pH increased with all devices. The highest pH values were observed with NPPV, diving regulator, Flow-Safe II and nasal high-flow but apparent hyperventilation was uncommon. The AirLife Open and the non-rebreather mask were the most comfortable, the SuperNO2VA and the nasal cannula the most uncomfortable devices. Conclusions: A standard diving regulator and the SuperNO2VA device were equally effective in providing highest physiologically possible pO2 as compared to nasal high-flow and NPPV.